Gender achievement and social, political and economic equality: a European perspective. Issue 1 (1st January 2017) - Ireson, Gren
Abstract: Differences in gender equality based on social, political and economic factors is cited, by some writers, as a contributory factor in the differentially greater achievement of boys in STEM subjects through the concept of gender stratification. Gender differences, especially in mathematics, have been linked directly to gender parity in wider society. Such a link is predicted by gender stratification via both the gender similarities and gender stratification hypotheses. However analysis by others appearsto support the hypothesis that the gender gap is smaller, in mathematics, when the society has a higher equality index. However, more recently, evidence, based on PISA outcomes from 2000 to 2009, reports that there is little or no correlation between the gender gap and wider equality. This paper takes up this analysis using PISA data from the 2012 round, for both science and mathematics, and the Global Gender Gap Index in a European context. The results cast doubts on any link between national gender equality and achievement in science or mathematics.